Interview with professor Rodrigo Canalli on artificial intelligence in the Brazilian Judicial Branch - Silva, Christine Oliveira Peter da; Meier, Ian Ferrare; Álvares, Luísa Cristina Vasconcelos Marimon; Lima, Lucas de Pádua Carvalho Mendes (My University, 2026)
Rodrigo Canalli is an Law clerk to a Justice of the Superior Labor Court (TST) and Professor at CEUB. Master in Law, State and Constitution from University of Brasília (UnB). Master in Competition, Innovation and Information Law from New York University School of Law. Former law clerk to a Justice of the Supreme Federal Court and Head-Advisor at the Artificial Intelligence Advisory Office within the same court.
Keywords: Artificial intelligence